Dekonstruksi Paradigma Radikal dalam Al-Quran - Nabilata, Lub Liyna (UIN Walisongo Semarang, 2018)
This paper aims to change the radical paradigm based on the verses of the Quran. Religion or verses of Quran often becomes a tool of legitimacy or justification of acts of violence. This research uses the methods of library research. From this research it is achieved that religious radicalism caused by the first war verses, often made up of legitimacy of violence and terrorism in Islam, the second, understanding the Jihad verses translated the war against the enemies of Islam, so that acts of violence against everything that was considered an enemy of Islam is the glorious JihadKeywords: radicalism, religion, violent ideological verses Abstrak Tulisan ini bertujuan untuk merubah paradigma radikal berdasarkan ayat-ayat Al-Quran. Agama atau ayat-ayat al-Qur’an sering menjadi alat legitimasi atau pembenaran atas tindakan kekerasan. Penelitian ini menggunakan metode library research. Dari penelitian ini didapatkan bahwa muculnya radikalisme agama disebabkan oleh pertama, ayat-ayat perang sering dijadikan legitimasi atas pro-kekerasan dan aksi terorisme dalam Islam., kedua, memahami ayat-ayat Jihad diartikan perang melawan musuh Islam, sehingga tindakan kekerasan terhadap segala sesuatu yang dianggap musuh Islam merupakan Jihad yang mulia Kata kunci: Radikalisme, Agama, Ayat-ayat Ideologi kekerasan